Gender in Human Rights and Transitional Justice (Crossing Boundaries of Gender and Politics in the Global South, 2018)
This volume counters one-sided dominant discursive representations of gender in human rights and transitional justice, and women's place in the transformations of neoliberal human rights, and contributes a more balanced examination of how transitional justice and human rights institutions, and political institutions impact the lives and experiences of women. Using a multidisciplinary approach, the contributors to this volume theorize and historicize the place of women's rights (and gender), situating it within contemporary country-specific political, legal, socio-cultural and global contexts. Chapters examine the progress and challenges facing women (and women's groups) in transitioning countries: from Peru to Argentina, from Kenya to Sierra Leone, and from Bosnia to Sri Lanka, in a variety of contexts, attending especially to the relationships between local and global forces.